TASK-BASED TEACHING IN THE ERA OF ARTIFICIAL INTELLIGENCE: CHALLENGES, AFFORDANCES AND PEDAGOGICAL IMPLICATIONS - Muzdalifah Mahmud (INDOPEDIA (Jurnal Inovasi Pembelajaran dan Pendidikan), 2026)
The use of artificial intelligence (AI) in the field of education has changed the way teachers teach and students learn. Despite the convenience it offers, AI provide us with opportunities as well as new challenges in education. This conceptual paper discusses how AI can support Task-Based Teaching (TBT), a teaching approach that encourages students to learn by completing meaningful and real-world tasks. The paper is a review of studies on  AI and TBT that have been done worldwide. The article proposes that AI should be used to strengthen, not replace, the main principles of TBT. AI can support learning by providing personalized feedback, learning assistance, and access to useful learning resources. However, it also brings about concerns such as plagiarism, overdependence on AI, digital inequality, ethical issues, and teacher readiness. Therefore, teachers should continue to play the main role in guiding learning, while AI serves as a learning assistant. Successful integration of AI into TBT requires responsible use, digital literacy, and thoughtful teaching practices.